Common haemostatic techniques used in surgical practice. (2nd August 2021) - Frew, Georgina H; Dick, Lachlan; Young, Jamie
Abstract : Intraoperative bleeding can be difficult to manage and is associated with worse patient outcomes. Good intraoperative haemostasis by the surgeon is a key factor in ensuring a bloodless field and reducing intraoperative blood loss. There is a myriad of mechanical, thermal and energy-based techniques available to use, each of which has their own benefits and drawbacks. The decision of which to use will depend on patient and procedural factors as well as the surgeon's preference. This article reviews techniques commonly used in surgical practice to maintain intraoperative haemostasis.